2017
DOI: 10.1016/j.jand.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Cost of Lifestyle Interventions Including Nutrition Education for Diabetes Prevention: A Systematic Review and Meta-Analysis

Abstract: Background Type 2 diabetes is a significant public health concern. With the completion of the Diabetes Prevention Program, there has been a proliferation of studies attempting to translate this evidence base into practice. However, the cost, effectiveness, and cost-effectiveness of these adapted interventions is unknown. Objective The purpose of this systematic review was to conduct a comprehensive meta-analysis to synthesize the effectiveness, cost, and cost-effectiveness of lifestyle diabetes prevention in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
108
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(125 citation statements)
references
References 104 publications
6
108
0
11
Order By: Relevance
“…Although there is currently no widely accepted cost effectiveness threshold for reduction in weight or waist circumference, the results of this analysis are comparable to ICERs calculated for the same health effects in other studies. In a recent systematic review, Sun et al reported that the lowest average cost per kg weight loss was $34.06 over 6 months, while the highest was $1,005.36 over 12 months [11]. As expected, because of the high cost of HE and resulting small cost difference between FBAS and HE, the ICERs reported in this study were on the lower end of the range of ICERs from similar studies.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Although there is currently no widely accepted cost effectiveness threshold for reduction in weight or waist circumference, the results of this analysis are comparable to ICERs calculated for the same health effects in other studies. In a recent systematic review, Sun et al reported that the lowest average cost per kg weight loss was $34.06 over 6 months, while the highest was $1,005.36 over 12 months [11]. As expected, because of the high cost of HE and resulting small cost difference between FBAS and HE, the ICERs reported in this study were on the lower end of the range of ICERs from similar studies.…”
Section: Discussionsupporting
confidence: 63%
“…The meta-analysis, as a whole, concluded that programs can lower implementation costs and still achieve clinically significant weight loss, the single most important factor in reducing diabetes incidence [7]. However, there are few translation studies that have evaluated the cost-effectiveness of lifestyle interventions [7, 11]. There is an even greater paucity of research on the cost-effectiveness of lifestyle interventions targeting African Americans, a high-risk group.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with usual care, the effect of a lifestyle intervention on HbA1c was limited when baseline values was ,7.0% (53 mmol/mol). Furthermore, in a review of the effect of nutrition therapy in prediabetes, HbA1c declined w0.3 percentage points compared with the effect of usual care (19).…”
Section: Discussionmentioning
confidence: 99%
“…Specific to type 2 diabetes mellitus (T2DM), dietary intake plays a critical role in the management of the disease. Providing dietary and lifestyle education focused on T2DM has resulted in improved self-management and a reduction in both hemoglobin A1c (HbA1c) and 2-hour blood glucose levels 57…”
Section: Introductionmentioning
confidence: 99%